Agonistic induction of PPARγ reverses cigarette smoke–induced emphysema - Shan, Ming; You, Ran; Yuan, Xiaoyi; Frazier, Michael V.; Porter, Paul; Seryshev, Alexander; Hong, Jeong-Soo; Song, Li-zhen; Zhang, Yiqun; Hilsenbeck, Susan; Whitehead, Lawrence; Zarinkamar, Nazanin; et al. (The Journal of Clinical Investigation, 2014)
The development of emphysema in humans and mice exposed to cigarette smoke is promoted by activation of an adaptive immune response. Lung myeloid dendritic cells (mDCs) derived from cigarette smokers activate autoreactive Th1 and Th17 cells. mDC-dependent activation of T cell subsets requires expression of the SPP1 gene, which encodes osteopontin (OPN), a pleiotropic cytokine implicated in autoimmune responses. The upstream molecular events that promote SPP1 expression and activate mDCs in response to smoke remain unknown. Here, we show that peroxisome proliferator–activated receptor γ (PPARG/Pparg) expression was downregulated in mDCs of smokers with emphysema and mice exposed to chronic smoke. Conditional knockout of PPARγ in APCs using Cd11c-Cre Ppargflox/flox mice led to spontaneous lung inflammation and emphysema that resembled the phenotype of smoke-exposed mice. The inflammatory phenotype of Cd11c-Cre Ppargflox/flox mice required OPN, suggesting an antiinflammatory mechanism in which PPARγ negatively regulates Spp1 expression in the lung. A 2-month treatment with a PPARγ agonist reversed emphysema in WT mice despite continual smoke exposure. Furthermore, endogenous PPARγ agonists were reduced in the plasma of smokers with emphysema. These findings reveal a proinflammatory pathway, in which reduced PPARγ activity promotes emphysema, and suggest that targeting this pathway in smokers could prevent and reverse emphysema.